Images of Muslims on lemonde.fr during the period of terrorist attacks in Europe in 2015-2016 - Ševčenko, Polina (Družboslovne razprave, 2019)
The purpose of this study was to analyse images of Muslims appearing in articles published from 2015 to 2016 on the website lemonde.fr. At this time, the country was faced with terrorist attacks that resulted in various government decisions and a complex emotional state of the nation. The study includes 617 articles from lemonde. fr, individually refined through 16 keywords. The quantitative and qualitative content analysis allowed for three main thematic categories of articles to be determined: Muslims as potential terrorists, the incompatibility of Islamic religious symbols with European values, and Islam as an obstacle to secularism in school. Muslims were represented as victims of discrimination or as criminals. These images negatively affected the perception of this religious minority in France and may have led to complications in intercultural communication.
Keywords: Analiza vsebine; Content analysis (Communication); Islam; Mass media; Množični mediji; Muslimani; Muslims